Temporal Discounting and Marketing Variables: Effects of Product Prices and Brand Informational Reinforcement - Oliveira-Castro, Jorge M . (Behav Anal, 2017)
By integrating the temporal discounting perspective, according to which the value of rewards is progressively discounted as a function of delay, and the Behavioral Perspective Model (BPM), according to which the purchase of products can produce utilitarian (directly obtained from use) and informational (social, mediated by others) reinforcing and punitive consequences, the present research investigated: 1) if temporal discounting would be better described by an exponential or a hyperbolic function; 2) if differently priced products would differ with respect to temporal discounting rates; and 3) if brands offering different levels of informational reinforcement would differ with respect to temporal discounting rates. In a first phase of the research, 73 undergraduate students evaluated brands of cell phone, tablet and TV set, in order to rank each brand according to the informational reinforcement level they offered. In a second phase, during an online purchasing simulation of these products, 51 students were asked to state how much they were willing to pay in order to anticipate product delivery, which was free after 21 days. Results indicated that the hyperbolic function fitted the data significantly better than the exponential function for two of the products, that products with higher prices showed lower temporal discounting rates than products with lower prices, and that brands associated with higher informational reinforcement showed higher temporal discounting rates. These findings suggest that there are complex interactive patterns of temporal discounting within- and between-products and that temporal discounting framework has great potential to inform research in consumer behavior and marketing.